X-Ray Crystallography and Biological Studies of Iron(II), Cobalt(II) and Nickel(II) Complexes Derived from Bidentate Schiff Bases - Mehta, B.H.; Joishar, Deepak (Asian Journal of Chemistry, 2016)
The aldehydes, salicylaldehyde and 5-nitrosalicylaldehyde were treated with o-phenylenediamine for the synthesis of Schiff base. The ligands, thus formed were used to synthesize Fe(II), Co(II) and Ni(II) complexes. Elemental analysis, molar conductivity, magnetic susceptibility, IR absorption spectra, thermogravimetric analysis characterized the ligand and the metal complexes. The elemental analysis reveals the metal : ligand stoichiometry for Ni(II) and Co(II) complexes are 1 : 1, while that of Fe(II) complex is also 1 : 1 with two water molecules. The XRD data can be indeed to monoclinic system for Ni(II) and Co(II) complexes, while orthorhombic system for Fe(II) complexes. The ligand and the metal complexes were also studied for their antibacterial and antifungal activity.